2021
DOI: 10.1016/j.vaccine.2021.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination willingness, vaccine hesitancy, and estimated coverage at the first round of COVID-19 vaccination in China: A national cross-sectional study

Abstract: Background Vaccination against coronavirus disease 2019 (COVID-19) has become an important public health solution. To date, there has been a lack of data on COVID-19 vaccination willingness, vaccine hesitancy, and vaccination coverage in China since the vaccine has become available. Methods We designed and implemented a cross-sectional, population-based online survey to evaluate the willingness, hesitancy, and coverage of the COVID-19 vaccine among the Chinese populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
123
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 138 publications
(135 citation statements)
references
References 21 publications
9
123
3
Order By: Relevance
“…A key role to determine whether herd immunity can be reached is played by the willingness-to-vaccine of the population. According to previous surveys on COVID-19 vaccine hesitancy, vaccine acceptance in China was estimated to vary between 60.4% and 91.3% for general population aged 18 years and above [29][30][31][32] , and may be even lower for older adults 32 and healthcare workers 33 . Similar estimates were obtained for several other countries including the UK (71.5%) 34 and the US (75.4%) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…A key role to determine whether herd immunity can be reached is played by the willingness-to-vaccine of the population. According to previous surveys on COVID-19 vaccine hesitancy, vaccine acceptance in China was estimated to vary between 60.4% and 91.3% for general population aged 18 years and above [29][30][31][32] , and may be even lower for older adults 32 and healthcare workers 33 . Similar estimates were obtained for several other countries including the UK (71.5%) 34 and the US (75.4%) 34 .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in line with previous studies which showed that individuals with greater COVID-19 vaccine hesitancy have reported greater concerns about vaccine safety generally [ 44 ], and vaccine attributes posed prevalent concerns due to the novelty of COVID-19 vaccines [ 6 ]. A large survey in China [ 45 ] showed that 35.5% of participants in January 2021 reported vaccine hesitancy, and its most prevalent reason was concern about the safety of the COVID-19 vaccine and the low efficacy of the vaccine. However, there is evidence of substantial variations in COVID-19 vaccine acceptance between countries and subgroups, as well as in psychosocial predictors of vaccine hesitancy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wang’s research showed similar results: that vaccine confidence rates increased with increasing age ( p < 0.05) and older people (age ≥ 65) showed the lowest rate of COVID-19 vaccine hesitancy. Additionally, distrust in the vaccine, the delivery system, and the government were all associated with younger age, which contributed to vaccine hesitancy [ 20 ].…”
Section: Discussionmentioning
confidence: 99%